Verification of Challenges and Threats in Normative Documents Regulating the Cybersecurity of The State - Bartlomiej TEREBINSKI (Communications of International Proceedings, 2022)
The article presents hazards and indicates opportunities and risks highlighted in the documents standardising cyberspace functioning. The author made an attempt to answer the following question: How are the state’s cybersecurity challenges and hazards characterised in normative documents? Since the emergence of the Internet, different countries have pointed out the growing significance of national regulations and international agreements on cyberspace nature. Cybersecurity is a vital area nowadays since it protects all data categories from theft and damage. It covers sensitive data, information enabling identifying a person, protected health information, personal data, intellectual property, data and governmental and sectoral ICT systems. The research problem concerns evaluation of standards used in Polish reality are supposed to present a general evaluation of the fitness, correctness and validity of cybersecurity challenges and hazards. For the analysis of the factual material, selected theoretical methods were used, such as analysis, synthesis, comparison and deductive inference. It allowed to put forward the thesis of a general increase in the risk of using the Internet, aggravated by global communication and using cloud services to store sensitive and personal data. The typically poor configuration of cloud services combined with increasingly sophisticated cybercriminals means a rising risk of successful cyberattacks and data violence. Without implementing legal acts and establishing specific cybersecurity programmes, no contemporary organisation can defend itself from attempted data security breaches, making it an easy target for cybercriminals.
Keywords: cybersecurity; hazards; challenges; cybersecurity strategy; national security